Preparation of polypropylene-based nanocomposites using nanosized MCM-41 as support andin situpolymerization - González, Darío M. (2016)
MCM-41 nanoparticles were used for preparing nanocomposites through the in situ polymerization of propylene. The performance of the catalytic system and the final properties of thematerials obtained are highly dependent on themethodology used for impregnation of the catalyst onto the support particles, and therefore an optimization study for the impregnation methodology of the catalyst (Me2Si(Ind)2ZrCl2)was carried out. Two differentmethodologieswere used; the results in terms of catalytic activity and polymer molecular masses indicated that the most promising one involved the pre-activation of the catalyst with the cocatalyst, methylaluminoxane, followed by impregnation onto the MCM-41 nanoparticles. Thus, an optimized route for the preparation of polypropylene nanocomposites achieving significant improvements in catalyst activity was developed. The nanocomposite materialswere characterized by GPC, TGA and DSC. The dispersion state and the size of the nanoparticles incorporated in the polypropylene matrix were investigated by transmission electron microcopy. Additionally, this methodology allows simultaneous control of the desired amount of support and the concentration of catalyst to be used in the in situ polymerization.